The Relationship Between Personality And Perceived Job Performance : A study among employees in an organization - Heng, Chin Siong; Wan Nor Maria, Wan Abdullah; Abang Ekhsan, Abang Othman; Sheilla Lim, Omar Lim; Philip Nuli, Anding (Universiti Malaysia Sarawak, UNIMAS, 2014)
This study examined the relationship between the “Big Five” Personality factors with perceived job performance. The sample involved employees from four faculties at a local university in Sarawak. From a total of 100 sets of questionnaires that were distributed, the researchers collected 85 sets from the respective respondents. The data were analyzed using Pearson Correlation Analysis to identify the relationship between extraversion, agreeableness, conscientiousness, neuroticism and openness with employee perceived job performance in a local public university. Stepwise Multiple Regression is used to determine the influence of the Five Personality factors on employee perceived job performance. The findings of this study showed that there is no relationship between personality factors of extraversion, agreeableness, conscientiousness and neuroticism on employee perceived job performance. However, openness has a moderate relationship with employee perceived job performance. The findings of this study may be used by management and human resource practitioners when they consider personality traits and employee performance. Advance steps can be taken to improve employee job performance and to develop quality and potential employees at the university level.